2015
DOI: 10.1179/1743284714y.0000000737
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deposition pressure on texture of pyrolytic graphite during chemical vapour deposition

Abstract: To investigate the influence of deposition pressure on the texture of pyrolytic graphite, a series of experiments were carried out. The pyrolytic graphites were fabricated at 2000°C with propylene as the carbon source and nitrogen as the carrier gas in a system pressure from 1·1 to 1·8 kPa. Results show that lowering the deposition pressure will increase the density and thin the growth cones. The reduce of deposition pressure will also cause an increasing in the degree of graphitisation extracted from X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It was found that the PyG growth rate was proportional to the pyrolysis temperature, the disorder of stacking was inversely proportional to the pyrolysis temperature, and the increase of temperature favors for the graphitization of PyG. While Zhu 9 studied the effect of the pressure and temperature on the microstructural changes of PyG prepared by CVD method and found that the increase in pressure was favorable for PyG initial growth. Zheng 10,11 investigated the effect of carbon source at different flow rates on the microstructure of carbon in carbon fiber growth pyrolysis carbon and found that the higher the flow rate, the better the growth quality.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the PyG growth rate was proportional to the pyrolysis temperature, the disorder of stacking was inversely proportional to the pyrolysis temperature, and the increase of temperature favors for the graphitization of PyG. While Zhu 9 studied the effect of the pressure and temperature on the microstructural changes of PyG prepared by CVD method and found that the increase in pressure was favorable for PyG initial growth. Zheng 10,11 investigated the effect of carbon source at different flow rates on the microstructure of carbon in carbon fiber growth pyrolysis carbon and found that the higher the flow rate, the better the growth quality.…”
Section: Introductionmentioning
confidence: 99%